Stress, diabetes, and infection: Syndemic suffering at an urban Kenyan hospital. (December 2015) - Mendenhall, Emily; Omondi, Gregory Barnabas; Bosire, Edna; Isaiah, Gitonga; Musau, Abednego; Ndetei, David; Mutiso, Victoria
Abstract: The complexity of sickness among Kenya's urban poor cannot be dissociated from how social and health problems become syndemic. Increasingly diabetes and other non-communicable diseases (NCDs) are emerging among low-income populations that also are most afflicted by social stress and infection. This article examines how social stress, psychological distress, and physical illness among patients in a public hospital in Nairobi, Kenya, produce syndemic suffering, defined by lived experiences of syndemic clustering such as diabetes with depression and infection. We recruited 100 urban public hospital patients, of which half were women, and half had type 2 diabetes from June to August 2014. We administered written informed consent and collected anthropometrics and blood samples before we conducted lengthy mixed qualitative and survey interviews. We analyzed social stress in narrative interviews using content analysis and evaluated social and physical contributors to mental distress with frequency tables and logistic regression. We found that people experienced diabetes through a complex social and medical framework, where social problems were cause and consequence to psychological and physical suffering. Women's narratives revealed more social suffering as well as more mental distress and somatic symptoms, including multi-morbidities, than men's. People with diabetes reported not only concurrent anxiety and depression but also common infections, including malaria, tuberculosis, and HIV/AIDS. Narratives reveal how NCDs concurrent with infections, and HIV in particular, produce financial challenges for patients, especially when HIV treatment is free and patients must pay out-of-pocket for diabetes care. Future studies should investigate syndemic clustering of infections and NCDs among low-income populations at the population-level. Highlights: Unique focus on low-income urban Kenyans' experiences living with type 2 diabetes. Moves beyond disease-specific models of diabetes. Reveals unique circumstances for those with diabetes and infection, including HIV/AIDS. Describes how gender, social problems and financial insecurities impede diabetes care. Argues that syndemic clustering of stress, diabetes, and infection complicates illness experiences.